Dynamic elasticities of tax revenue: Evidence from the Czech Republic - Tomáš Havránek; Zuzana Havránková; Jiří Schwarz (Charles University in Prague, Institute of Economic Studies (IES), 2015)
Key parameters for the modeling of public finances are tax revenue elasticities with respect to tax bases. Yet the existing studies estimating these elasticities for emerging countries disregard the effects of tax reforms on tax revenue, which renders their estimates inconsistent. We use a unique data set from the Czech Republic to account for the effects of reforms and estimate both short- and long-run tax revenue elasticities. Our results suggest that the long-run elasticities are 1.4 for wage tax, 0.9 for value added tax, and 1.7 for profit tax. The adjustment process for value added tax is fast, but for the remaining two categories it is important to distinguish between the short- and long-run elasticities: the initial response of revenue to changes in the bases is weak. In the case of wage tax it takes half a year for the elasticity to surpass unity.
Keywords: H24; H25; H27; 330; tax revenue; tax base; elasticity; error correction models